Government in the Twilight Zone : Volunteers to Small-City Boards and Commissions - Baker, John R., 1959- (Book collections on Project MUSE., 2015)
"Drawing on a unique and extensive set of survey data from board members, mayors, and city councilors in sixty cities across six states, Government in the Twilight Zone significantly expands our knowledge of small-city boards and politics"--Page 4 of cover.